Scanning and Skimming Strategies to Assists Students in English Reading Texts - Maili, Sjafty Nursitti NP (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
Reading is a skill of English learning. First, it makes students have a great knowledge. Second, to help students improve their writing. Third, it can increase English vocabulary. Scanning and skimming are strategy suitable used to assists students in English reading text. The objective of this study is to know the effectiveness of scanning skimming strategy. The method that researcher used is qualitative method which researcher take the data from some journal, after that we put in the table the author, journal’s name, result, the next we analysis and get the conclusion. The results are all of journals that the researcher collected support the scanning and skimming as strategy English teacher to motivate students and to make students understand in reading text.